Methane production in the stems of living trees in subtropical forests - Zhi-Ping Wang; Josep Barba; Jian-Guo Xue; Xiang-Cheng Mi; Ang Li; Zhen-Ying Huang; Shi-Jie Han (Planta, 2026)

Enhanced lithium extraction from high-sodium brines: Modification of a manganese-based ion sieve using hydroxylated graphene and graphene oxide - Ang Mi; Xinbo Qin; Fei Zhang; Rongping Yun; Youjing Zhao; Min Wang; Xu Xiang (Desalination, 2025)

Distinct responses and range shifts of lizard populations across an elevational gradient under climate change - Zhong‐Wen Jiang; Liang Ma; Chun‐Rong Mi; Shi‐Ang Tao; Fengyi Guo; Wei‐Guo Du (Global Change Biology, 2023)
Ongoing climate change has profoundly affected global biodiversity, but its impacts on populations across elevations remain understudied. Using mechanistic niche models incorporating species traits, we predicted ecophysiological responses (activity times, oxygen consumption and evaporative water loss) for lizard populations at high‐elevation (

Impact of agricultural land use on aquatic insect assemblages in the Garonne river catchment (SW France) - Mi-Young Song; Fabien Leprieur; Alain Thomas; Sithan Lek-Ang; Tae-Soo Chon; Sovan Lek (Aquatic Ecology, 2009)